An IT person’s view on New Digital Storytelling - Ewa Baumgarten (2014)
This document is an attempt to bridge the communication gap between IT people on the one hand and journalists employing digital technologies on the other. It is supposed to create a mutual understanding of the situation of their counterpart as well as an examination of the current status quo, the common working tools and environments and the needs and requirements for journalism in the digital age. Some possible elds of development for new narrative structures are highlighted throughout the thesis.
Keywords: New Digital Storytelling; bridging technology